Penerapan Pendekatan Open Ended untuk Meningkatkan Pemecahan Masalah pada Mata Pelajaran Matematika Kelas V SD - Teguh Yunianto; Maratul Qiftiyah; Tina Malinda; Nita Septiani (Al Mufid, 2023)
This research is based on the low level of problem-solving, in South Lampung. The saturation of students in learning usually causes displeasure towards the lesson, one of the subjects that some elementary school students really avoid is mathematics. Particularly at SDN 5 Karang Anyar Jati Agung, South Lampung, the use of an open-ended approach has not been implemented. From the problems found, solving the problem can be realized in the form of learning activities by applying an open-ended approach at SDN 5 Karang Anyar, Jati Agung, South Lampung. The implementation method uses two stages, namely: the preparation stage and the implementation stage. The results of the study show that the use of an open-ended approach can improve mathematical problem-solving for fifth-grade students at SDN 5 Karang Anyar Jati Agung South Lampung in the 2022 academic year